Energy requirements of puppies of two different breeds for ideal growth from weaning to 28 weeks of age. Issue 1 (22nd November 2011) - Dobenecker, B.; Endres, V.; Kienzle, E.
Summary To ensure an optimal growth is crucial in raising healthy dogs, especially in large and giant breeds. Dogs with a moderate growth velocity tend to have lesser problems with developmental orthopaedic diseases than those with forced or maximum weight gain. In this study, the energy needs of growing dogs from two different breeds (Beagles as a medium‐size breed and Foxhound crossbreds as a large‐size breed) to ensure a growth development as recommended by the National Research Council (NRC) were determined at the age of 6–28 weeks. After weaning at the age of 6 weeks, the food rations sufficient to meet the energy requirements of each individual puppy were adjusted every other day according to growth level, guaranteeing a development consistent with the recommended weight curve for the respective breed size. The food and therefore energy intake of the puppies was registered daily; it ranged from 0.72 to 2.34 times the maintenance requirements with little effect of age. During the whole period, however, there was a consistent breed difference: Foxhound‐Boxer‐Ingelheim Labrador crossbreds (FBIs) had higher energy intakes expressed as multiples of maintenance than Beagles, suggesting that during the major period of growth, the energy requirement is not a function of age. Adult Beagles and FBIs showed similar differences in energy requirements as already during growth as shown in this study. This indicates that breed differences in energy requirements have already to be taken into account during growth. On the other hand, the results showed clearly lower energy needs for growth in these two different breeds than recommended in the NRC.